A Person-by-Situation Approach to Emotion Regulation - Troy, Allison S.; Shallcross, Amanda J.; Mauss, Iris B. (Psychological Science, 2013)
Emotion regulation is central to psychological health. For instance, cognitive reappraisal (reframing an emotional situation) is generally an adaptive emotion-regulation strategy (i.e., it is associated with increased psychological health). However, a person-by-situation approach suggests that the adaptiveness of different emotion-regulation strategies depends on the context in which they are used. Specifically, reappraisal may be adaptive when stressors are uncontrollable (when the person can regulate only the self) but maladaptive when stressors can be controlled (when the person can change the situation). To test this prediction, we measured cognitive-reappraisal ability, the severity of recent life stressors, stressor controllability, and level of depression in 170 participants. For participants with uncontrollable stress, higher cognitive-reappraisal ability was associated with lower levels of depression. In contrast, for participants with controllable stress, higher cognitive-reappraisal ability was associated with greater levels of depression. These findings support a theoretical model in which particular emotion-regulation strategies are not adaptive or maladaptive per se; rather, their adaptiveness depends on the context.